Quantitation of plasma thiamine, related metabolites and plasma protein oxidative damage markers in children with autism spectrum disorder and healthy controls. (1st November 2016) - Anwar, Attia; Marini, Marina; Abruzzo, Provvidenza Maria; Bolotta, Alessandra; Ghezzo, Alessandro; Visconti, Paola; Thornalley, Paul J; Rabbani, Naila
Abstract: Aims/hypothesis: To assess thiamine and related metabolite status by analysis of plasma and urine in autistic children and healthy controls, correlations to clinical characteristics and link to plasma protein markers of oxidative damage. Methods: 27 children with autism (21 males and 6 females) and 21 (15 males and 6 females) age-matched healthy control children were recruited. The concentration of thiamine and related phosphorylated metabolites in plasma and urine and plasma protein content of dityrosine, N-formylkynurenine and 3-nitrotyrosine was determined. Results: Plasma thiamine and thiamine monophosphate concentrations were similar in both study groups (median [lower–upper quartile]): autistic children – 6.60 nM (4.48–8.91) and 7.00 nM (5.51–8.55), and healthy controls – 6.82 nM (4.47–7.02) and 6.82 nM (5.84–8.91), respectively. Thiamine pyrophosphate (TPP) was decreased 24% in autistic children compared to healthy controls: 6.82 nM (5.81–8.52) versus 9.00 nM (8.41–10.71), p < .01. Urinary excretion of thiamine and fractional renal clearance of thiamine did not change between the groups. No correlation was observed between clinical markers and the plasma and urine thiamine concentration. Plasma protein dityrosine content was increased 88% in ASD. Other oxidative markers were unchanged. Conclusions/interpretation: Autistic children had normal plasma and urinary thiamine levels whereas plasma TPP concentration was decreased. The latter may be linked to abnormal tissue handling and/or absorption from gut microbiota of TPP which warrants further investigation. Increased plasma protein dityrosine may reflect increased dual oxidase activity in response to change in mucosal immunity and host–microbe homeostasis.